Growth of Gmelina Seedling with Various Compost Fertilizer in Ex-Gold Mining Land Media - Basuki Wasis; Nuri Fathia (Institut Pertanian Bogor (IPB University), 2011)
Mining activities could have negative impacts on the environment if the tailings produced were not processedproperly. Non-economic tailing is a composite of various minerals (heavy metal) with sandy texture. Environmental impacts that might occur as a result of poor processing of tailings is a disruption of natural ecosystems as indicated by a decline in quality and productivity of the environment as a result of changes in soil morphology and physical properties, chemical, and biological properties. One vegetative technique that could be applied to rehabilitate degraded land is re-vegetation with the application of fertilizer. Compost could improve the physical properties, chemical, and biological properties of soil. Compost was also an agent of bioremediation so that toxic heavy metals elements in growing medium could be eliminated or reduced. The experimental design used in this study was Completely Randomized Design with compost applications consisting of 4 levels of treatment with each level of treatment consisting of 3 replications, each replication consisted of one gmelina seedling. Research showed that the application of compost would significantly affect the growth of gmelina’s height, but not significantly affected the diameter growth. Single-dose effect of 30 g of compost would significantly affect the seedling’s height. The combination of planting and fertilizing glemina using compost could be recommended in an effort to reclaim land of ex-gold mining.